A stochastic model of asset pricing function with additive effects series for capital market prices - Amadi*, I.U.; Ebakpa†, L.E.; Azor‡, P.A. (International Journal of Mathematical Analysis and Modelling, 2023)
In this paper, a combination of two stochastic systems namely: Stochastic Differential Equation (SDE) and Stochastic Delay Differential Equation (SDDE) respectively were considered. A closed form analytical solutions were presented in details which determined asset values through additive effects series. The validity of the analytical solution were obtained and verified using initial stock prices; which were explicitly analysed using Kolmogorov-Smirnov and results showed that the two asset values do not come from a common distribution. Finally, the impressions of other key stock quantities were discussed and graphical results presented using MATLAB.